ANALISIS STRATEGI KOMUNIKASI DAN LOYALITAS KONSUMEN TERHADAP PEMASARAN SMARTPHONE DI KOTA SORONG PAPUA BARAT DAYA (STUDI KASUS PENJUALAN HP MEREK OPPO) - Rande, Elisabeth; Komber, Mervin I.S.; Irwan, Andi (POLITEKNIK LP3I JAKARTA, 2026)
This study aims to analyze the influence of communication strategy and consumer loyalty on marketing improvement. The research employs a quantitative approach with a survey method using questionnaires distributed to 100 respondents. Data were analyzed using validity and reliability tests, regression analysis, t-test, F-test, as well as R Square and regression coefficient (B) analysis. The results indicate that consumer loyalty has a significant and dominant effect on marketing improvement, while communication strategy does not have a significant partial effect. However, simultaneously, both variables have a significant effect on marketing improvement. The R Square value of 0.957 shows that 95.7% of the variation in marketing improvement can be explained by these two independent variables. These findings emphasize the importance of strengthening consumer loyalty as a primary focus in marketing strategies, even though communication strategies still need to be evaluated and effectively integrated. This study is limited by the number of variables and sample size, and does not account for other external factors that may influence the results. Suggestions for future research include expanding the variables studied, increasing the number of respondents, and utilizing qualitative approaches to gain a deeper and more comprehensive understanding of consumer behavior and the effectiveness of marketing strategies.